Peran Sukuk Negara dalam Pembiayaan Infrastruktur - Rizky Suci Ramadayanti; Dedy Mainata; Angrum Pratiwi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Sukuk are securities issued under sharia principles, as evidence of the participation in the State Sharia Securities/Surat Berharga Syariah Negara (SBSN) assets, either in rupiah or foreign currency. Sukuk is a proportional representation of ownership of an asset for a certain period of time with risksand returns associated with cash flow through underlying asset in the hand of investors. This paper describes the overview of the role of sukuk in infrastructure financing in Indonesia. Sukuk has played a significant role for infrastructure development in Indonesia. Indonesia’s infrastructure budget allocation gradually increased. A number of projects listed in the Anggaran Pendapatan dan Belanja Negara (APBN) are selected specially financed by sukuk. Since the issuance of project financing sukuk has doubled until this year. This is an important concern for the government that sukuk turned out to be an important financial instrument in Indonesia’s infrastructure development.